The Adaptive Neuroplasticity Hypothesis of Behavioral Maintenance - Janey C. Peterson (Neural Plasticity)
Physical activity is a seemingly simple and clinically potent method to decrease morbidity and mortality in people with coronary heart disease (CHD). Nonetheless, long-term maintenance of physical activity remains a frustratingly elusive goal for patients and practitioners alike. In this paper, we posit that among older adults with CHD, recidivism after the initiation of physical activity reflects maladaptive neuroplasticity of malleable neural networks, and people will revert back to learned and habitual physical inactivity patterns, particularly in the setting of stress or depression. We hypothesize that behavioral interventions that successfully promote physical activity may also enhance adaptive neuroplasticity and play a key role in the maintenance of physical activity through the development of new neuronal pathways that enhance functional ability in older adults. Conversely, without such adaptive neuroplastic changes, ingrained maladaptive neuroplasticity will prevail and long-term maintenance of physical activity will fail. In this paper we will: (1) describe the enormous potential for neuroplasticity in older adults; (2) review stress and depression as examples of maladaptive neuroplasticity; (3) describe an example of adaptive neuroplasticity achieved with a behavioral intervention that induced positive affect in people with CHD; and (4) discuss implications for future work in bench to bedside translational research.